A Gold Reserve and the Currency - Theodore H. Boggs (Canadian Institute of Mining, Metallurgy and Petroleum, 1925)
The battle of the gold standard is not limited to one country alone, or even to a single group of countries. It is being waged merrily in many important commercial and industrial quarters. Though it is not always a practical issue calling for immediate attention, it is none the less, quite widely, engaging the thought of bankers and other students of finance. The controversy arises, in the last analysis, because of the desire of men to secure a stable currency. There are two ways of restoring a reasonably stable currency system: (1) the re-establishment of the gold standard, or (2) the deliberate and artificial management of a paper currency. Both systems are well known. The gold standard was in use prior to the war in the principal commercial countries. A currency of inconvertible paper has been at times employed in the past in various countries; for example in Britain from 1797 to 1821, and in the United States from 1862 to 1879. The gold standard, as all are aware, implies the selection of gold as the standard of value. The unit of value is a fixed weight of gold and, so long as the standard remains unimpaired, all other means of payment are maintained at a parity with standard gold coins. And gold coins alone constitute the standard money, inasmuch as their value as bullion equals their value as coins. Under the gold standard this would not be true of any other form of money, although all other varieties of money, including bank notes, government notes and silver coins would be freely convertible into gold money. Strictly speaking, the gold standard also implies that the gold money in turn shall itself be freely convertible, through melting, into gold bullion and freely exportable.